Answer:
1
Step-by-step explanation:
b= -2, b2 +6b +9
=-2(2)+6(-2)+9
=-4-12+9
=4+9-12
=13-12
=1
Answer is 4 :) I hope it help you.
Answer:
two to the five sixths power
Step-by-step explanation:
![\sqrt{2} *\sqrt[3]{2} =2^{\frac{1}{2} }*2^{\frac{1}{3} } = 2^{\frac{1}{2} +\frac{1}{3}}=\\=2^{\frac{5}{6} }](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D%20%2A%5Csqrt%5B3%5D%7B2%7D%20%3D2%5E%7B%5Cfrac%7B1%7D%7B2%7D%20%7D%2A2%5E%7B%5Cfrac%7B1%7D%7B3%7D%20%7D%20%3D%202%5E%7B%5Cfrac%7B1%7D%7B2%7D%20%2B%5Cfrac%7B1%7D%7B3%7D%7D%3D%5C%5C%3D2%5E%7B%5Cfrac%7B5%7D%7B6%7D%20%7D)
Step-by-step explanation:
the right equation is :
y-y1=m(x-x1)
y+3=3(x+4)
y+3= 3x+12
y=3x+12-3
y=3x+9
Answer:
r = √98
Step-by-step explanation:
angle A and the diameter form an isosceles right triangle, with OA as the hypotenuse and r as the other sides. You can then make and solve an equation from the Pythagorean Theorem:
r^2 + r^2 = 14^2
2r^2 = 14^2
2r^2 = 196
r^2 = 98
r = √98